The relationship between severity of disease and vitamin D levels in children with atopic dermatitis - Su, Ozlem; Bahalı, Anıl Gülsel; Demir, Ayşegül Doğan; Ozkaya, Dilek Biyik; Uzuner, Selçuk; Dizman, Didem; Onsun, Nahide (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disorder. Vitamin D is a liposoluble vitamin synthesized mainly in the skin. Vitamin D has several effects on the skin. Aim : To assess the serum level of vitamin D in children with AD and determine its relation to AD severity. Material and methods : Sixty patients with AD were enrolled in the study. We evaluated disease severity using the SCORing Atopic Dermatitis (SCORAD) index. The control group consisted of 37 healthy subjects. Results : The mean serum concentration of 25(OH)D3 in patients with AD was not statistically different from control subjects (p = 0.065). The vitamin D level was significantly lower in moderate and severe AD compared with mild AD, and this difference was statistically significant (p = 0.001 and p = 0.004). Vitamin D showed a negative correlation with serum total IgE levels (p = 0.007). There was no significant correlation between total IgE levels and SCORAD scores (p = 0.089). Conclusions : This study suggests that a low serum vitamin D level is inversely associated with severity of AD in children. Vitamin D has not been included in the routine treatment of AD because of the conflicting results of various studies. Thus, there is a need for more detailed and prospective studies.